The Apocalyptic Vision of Jesus According to the Gospel of Matthew: Reading Matthew 3:16-4:11 Intertextually - David Mathewson (Tyndale Bulletin, 2011)
There has been much discussion on the relationship of Jesus to apocalyptic. What has been missing is a demonstration that Jesus participated in what is at the heart of literature labeled ‘apocalyptic’: a visionary experience of a transcendent reality. This article argues that Jesus’ post-baptismal experience and the temptation narrative that follows, particularly as recorded in Matthew 3:16–4.11, portray Jesus as undergoing such an apocalyptic visionary experience which resembles closely the visionary experience of early Jewish and Christian apocalypses. Thus, with the opening of the heavens to the final temptation, Matthew 3:16–4.11 depicts a third person account of a sustained visionary experience modeled intertextually after classic apocalyptic seers (Ezekiel, Isaiah, Enoch). Jesus’ apocalyptic vision functions to authenticate Jesus’ role as divine spokesperson for God and provides a perspective for the struggle that will ensue in the rest of Matthew.